Food servcies and catering management - Saxena, R. P. (New Delhi, 2010)
Food service or catering industry defines those businesses, institutions, and companies responsible for any meal prepared outside the home. This industry includes restaurants, school and hospital cafeterias, catering operations, and many other formats. The companies that supply food service operators are called food service distributors. Food service distributors sell goods like small wares (kitchen utensils) and bulk foods. Some companies manufacture products in both consumer and food service versions. The consumer version usually comes in individual-sized packages with elaborate label design for retail sale. The food service version is packaged in a much larger industrial size and often lacks the colourful label designs of the consumer version.
Keywords: Caterers and catering; Food service